The Hematological and Blood Chemical Parameters of the Female Fat Tail Sheep Raised with Fermented Complete Feed Management - Sarmin Sarmin; Amelia Hana; Pudji Astuti; Claude Mona Airin (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The study aimed at evaluating the hematological and chemical parameters of the blood of female fat tail sheep raised with fermented complete feed (CF) management. It used 40 adult female fat tail sheep age 24-36 months and body weight in 30-35 kg and 3-4 of body condition score, which was raised in the individual stall with fermented complete feed (CF) management. Samples of blood were drawn once from the jugular vein before feeding in the morning. The results of hematological parameters were RBC (12.11±2.18 x106/µL), hemoglobin (12.40±1.96 g/dL), hematocrit (36.49±5.47%), MCV (30.46±3.38 fL), MCH (10.30±0.75 pg), MCHC (34.00±1.86 g/dL), eosinophils (3.15±7.70%), neutrophils (7.13±14.90%), lymphocytes (11.93±23.85%), and monocytes (0.30±0.88%). The results of chemical parameters were sodium (147.58±3.75 mmol/L), chloride (106.51±3.12 mmol/L), magnesium (3.66±1.38 mg/dL), albumin (3.36±0.31 g/dL) and glucose (40.28±9.12 mg/dL). The results of hematological and chemical parameters in the study could be the reference in monitoring the health of the adult female fat tail sheep raised with the fermented complete feed (CF) management.